Novel Methicillin-Resistant Staphylococcus aureus CC8 Clone Identified in a Hospital Setting in Armenia - Jamrozy, Dorota; Misra, Raju; Xu, Zhen; Ter-Stepanyan, Mary M.; Kocharyan, Karine S.; Cave, Rory; Hambardzumyan, Armen Dz; Mkrtchyan, Hermine V. (Frontiers in Microbiology, 2019)
Whole genome sequencing (WGS) of methicillin-resistant Staphylococcus aureus (MRSA) has been sparse in middle- and low-income countries, therefore its population structure is unknown for many regions. We conducted a pilot surveillance of MRSA in the maternity ward of a teaching hospital in Armenia, to characterise the genotypes of circulating MRSA clones. In total, 10 MRSA isolates from a hospital environment (n=4) and patients (n=6) were recovered between March and May 2015 and April and May 2016, respectively. WGS analysis showed that the isolates belonged to two clonal complexes (CC): CC8 (n = 8), CC30 (n = 2). MRSA CC30 isolates carried SCCmec type IVa, whereas MRSA CC8 revealed SCCmec type V, which contained a CRISPR/Cas array and showed a high similarity to SCCmec found in coagulase negative staphylococci. All but one MRSA CC8 isolates carried a plasmid identical to the pSK67 and four also carried a pathogenicity island similar to SaPI5. Phylogenetic analysis showed that the MRSA CC8 isolates formed a monophyletic cluster, which emerged around 1995 and was distinct from representatives of globally-distributed MRSA CC8 lineages. WGS characterisation of MRSA in countries with no previous S. aureus genomic surveillance can therefore reveal an unrecognised diversity of MRSA lineages.